Faktor Maternal dan Pola Makan dengan Kejadian Kekurangan Energi Kronik pada Ibu Hamil di Wilayah Kerja UPTD Puskesmas Kangkung I - Hikmah, Hanifatul; Puji, Yuni; Istioningsih, Istionigsih (Jurnal Kebidanan Malakbi, 2020)
Chronic energy deficiency is a condition in which a person's nutritional status is poor due to a lack of intake of energy sources that contain macro nutrients that last for long or years. The purpose of this study was to determine the relationship between Factor Characteristics, Maternal Factors and Eating Patterns and Chronic Energy Deficiency (CED) Events in Pregnant Women. This study used a correlational descriptive design, with cross sectional approach. The sampling technique is Non Probability Sampling with a sample of 150 pregnant women. Results shows there was a significant relationship between the age of pregnant women (p value of 0.002), parity (p value of 0.011), education (p value of 0,000), the history of complications (p value of 0.030), eating patterns (p value of 0,000), and the incidence of CED. There is no significant relationship between maternal family income and the incidence of CED, the p value is 0.063. Research result prove there are still 10,7% of pregnant women who spend Chronic Energy Deficiency and there are 10,7% of those who have poor diet, expect pregnant women to pay attention and meet their nutritional needs, to avoid Chronic Energy Deficiency (CED) and be active in finding information and asking lots of questions that understand more about health, especially related to Chronic Energy Deficiency problems.